Pengaruh Penggunaan Media Bahan Ajar Elektronik Booklet Audio Visual (E-BAV) untuk Meningkatkan Motivasi dan Hasil Belajar PPKn Kelas XI SMK Islam Kanigoro - Prasetyo, Dony Ambar; Rarasati, Ida Putri; Baihaqi, M. Iqbal (Transpublika Publisher, 2025)
Lecture learning is the dominant method and is carried out without taking into account the possibility of using other learning models depending on the type of teaching material, so that students are passive and bored during learning. Conventional learning is considered as monotonous learning because only the teacher plays an active role in providing information, while students only show questioning skills and record what the teacher says. This study aims to determine the effect of EBAV (Electronic Audiovisual Booklet) teaching materials on PPKn learning motivation of class XI students of Kanigoro Islamic Vocational School and to determine the effect of EBAV (Electronic Audiovisual Booklet) teaching materials on PPKn learning outcomes of class XI students of Kanigoro Islamic Vocational School. The research method used in this study is the quantitative research method. The results of this study are that there is an influence of EBAV (Electronic Audiovisual Booklet) teaching materials on the learning motivation of PPKn students of class XI SMK as evidenced by the calculation of the hypothesis with simple linear regression with a p-value of 0.000 <0.05 and there is also the effect of EBAV (Electronic Audiovisual Booklet) teaching materials on PPKn learning outcomes for class XI SMK students are proven by calculating the hypothesis with simple linear regression with a p-value of 0.001 <0.05.